System based on an inertial measurement unit for accurate flight time determination in vertical jumps - Moreno-Pérez, J. A.; Ruiz-García, I.; Navarro-Marchal, I.; López-Ruiz, N.; Gómez-López, P. J.; Palma, A. J.; Carvajal, M. A. (Sensors, 2023)
The world of elite sports has always been characterized by intense competition, where victories are often determined by minimal differences. This means that every little detail in the preparation of top-level athletes is crucial to their performance at the highest level. One of the most significant aspects to monitor is the jumping capacity, as it enables the measurement of performance, progression, and helps prevent injuries. Herein, we present the development of a system capable of measuring the flight time and height reached by the user, reporting the results through a smartphone using an Android ad-hoc application, which handles all the data processing. The system consists of an affordable and portable circuit based on an accelerometer. It communicates with the smartphone via UART using a Bluetooth module, and its battery provides approximately 9 h of autonomy, making it suitable for outdoor operations. To evaluate the system`s precision, we conducted performance tests (counter-movement jumps) with seven subjects. The results confirmed the system`s potential for monitoring high-level sports training sessions, as the average deviation obtained was only 2.1% (~0.01 s) in the analysis of flight time and 4.6% (~0.01 m) in jump height.